KUALITAS PELAYANAN PUSKESMAS KAMPAR KIRI KECAMATAN KAMPAR KIRI - Vedrianto "; Harapan Tua R.F.S (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Quality Services of Kampar kiri Comunnity Health Center At Kampar Kiri District of Kampar as places that serve the public, the health service is often in the spotlight left Kampar district community. Convoluted and complicated service procedures, often exceeding the settling time, speed and accuracy in providing services to the public. The purpose of this study was to determine the quality of service and determine the factors that affect the quality of service sub-district health centers Kampar Kiri of Kampar.This research uses the theory by Parasuraman, Zeithhaml, and Leonard Berry in Harbani Pasolong (2007), which consists of Tangible, Reliability, responsivenes, Assurance, Empathy. The method used is qualitative research with data collection technique through interview, observation and documentation.The results of this study show that, the quality of service sub-district health centers left Kampar Kampar Kampar district left yet either, because there are several dimensions such as physical evidence, reliability, responsiveness, assurance and empathy has not been good. Of the five dimensions, but the dimensions are obtained guarantees good ratings, in this dimension the service provider has been able to provide assurance that they are skilled employees to take care of the affairs of the applicant, and also have the knowledge to answer and resolve any questions and complaints. As for the other four dimensions left the clinic kampar districts left Kampar Kampar district not meet the desired quality of society.Keyword: Service, Quality of Service